Between parent and child : the bestselling classic that revolutionized parent-child communication - Ginott, Haim G.; Ginott, Alice; Goddard, H. Wallace (New York : Three Rivers Press, 2003)
Offers advice to a current generation of parents on how to develop empathetic yet disciplined child rearing skills that place an emphasis on good communication and avoid negative reinforcements.
The code of communication : parent-child conversations -- The power of words : better ways to encourage and guide -- Self-defeating patterns : there's no right way to do a wrong thing -- Responsibility : transmitting values rather than demanding compliance -- Discipline : finding effective alternatives to punishment --A day in a child's life -- Jealousy : the tragic tradition -- Some sources of anxiety in children : providing emotional safety -- Sex and human values : sensitive handling of an important subject -- Summing up : lessons to guide your parenting -- Epilogue.
Includes bibliographical references (p. [221]-224) and index.
Keywords: Child rearing; Parent and child; Emotions in children; Empathy